Standardizing, Segmenting and Tenderizing Letters and Improving the Quality of Envelope Images to Extract Postal Addresses - Milad Shirmohammadi; Karim Faez; Hassan Khotanlou (Institute of Advanced Engineering and Science, 2012)
In most mechanized postal systems, envelopes are scanned based on the postal standard using mechanical instruments. In the standard format, the image of envelopes lacks tilts, lines are along the horizontal axis and words are placed in a correct and non-oblique manner. In this article a new algorithm for rotating, segmentation and Tenderizing Letters for standardizing and increasing the quality of an envelope has been presented, which can be used in all text identification systems as three successful pre-processing algorithms. In the algorithm proposed, letters with any forms and tilts during scanning were rotated and standardized by applying a simple two-step algorithm based on what was written on the envelope without requiring the calculation of tilt angle. After standardization, the main regions of the image were specified using the histogram information. Then, in a simple algorithm, the candidate points from the pixels related to the text on the envelope were selected and quality improvement and tenderization were done on the main regions of the image. The advantaged of the proposed algorithm included No need for additional mechanical equipment, less calculation, simplicity and consideration of the structure of words on the envelope in all preprocessing phases.DOI:http://dx.doi.org/10.11591/ijece.v2i3.342